Eva grafted maleic anhydride modified epoxy resin functionalized polymer and method of making same
Patent Information
- Application Number
- CN202611210231.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-11-03
AI Technical Summary
Existing EVA materials suffer from problems such as unstable grafting reaction, broken molecular chains, uncontrollable free radical release rate, and insufficient interfacial compatibility during polar modification, leading to a decline in material performance and making it difficult to meet the requirements of high-filler and high-flame-retardant systems.
EVA was melt-grafted and modified using a composite free initiation system. A branched and local network structure was constructed through the ring-opening reaction of maleic anhydride and epoxy resin. Continuous preparation was achieved using a twin-screw reactive extrusion process.
It improves the polarity, interfacial compatibility and melt strength of the material, enhances processing performance, is suitable for high-filler and high-flame-retardant systems, is suitable for industrial production, and has good interfacial adhesion and thermal stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material modification, specifically to an EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer and its preparation method. Background Technology
[0002] Ethylene-vinyl acetate copolymer (EVA) is a thermoplastic polymer formed by copolymerizing ethylene monomers and vinyl acetate monomers. Because EVA combines the processing properties of polyethylene with the flexibility of rubber materials, it is widely used in cable insulation materials, hot melt adhesives, packaging films, shoe materials, photovoltaic encapsulation, and modified plastics. The higher the vinyl acetate content in EVA, the better its polarity, flexibility, and low-temperature performance; while lower vinyl acetate content results in a material closer to the characteristics of polyethylene, exhibiting higher crystallinity and rigidity. However, although EVA itself has a certain degree of polarity, its polarity level is still insufficient to meet the interfacial compatibility requirements with highly polar polymers. When EVA is applied to polyamide, polyester, inorganic filler, high flame retardant systems, and low-smoke halogen-free cable materials, insufficient interfacial compatibility often leads to problems such as material delamination, decreased mechanical properties, poor processing stability, and insufficient long-term durability. Therefore, further polar functionalization modification of EVA has become an important research direction in the field of polymer modification.
[0003] Currently, common methods for polar modification of EVA include solution grafting, melt grafting, and copolymerization. While solution grafting achieves high grafting efficiency, it suffers from complex processes, high equipment investment, difficulties in solvent recovery, and high environmental impact. Copolymerization modification typically relies on large-scale polymerization equipment, has high technological barriers, and is not conducive to flexible industrial production. Therefore, melt radical grafting, due to its simple equipment, mature process, and suitability for continuous industrial production, has become the most promising modification route.
[0004] However, the following problems still exist in the traditional EVA-g-MAH system: (1) MAH self-polymerization, increased side reactions and unstable grafting efficiency are prone to occur during the grafting reaction; (2) The high temperature free radical environment is prone to EVA molecular chain breakage, degradation or even cross-linking, resulting in a decrease in material processing performance; (3) The free radical release rate of the traditional single initiator system is difficult to control, and it is easy to form a local free radical concentration that is too high; (4) Although the polarity of grafted EVA-g-MAH is improved, its molecular structure is still mainly linear, and the enhancement effect in high-filling, high-flame-retardant or high-interface-demand systems is limited; (5) There is still room for further improvement in the melt strength, interfacial stability and thermal stability of existing materials.
[0005] In recent years, the development of reactive extrusion technology has provided new directions for the structural control of functionalized polymers. In particular, the ring-opening reaction between anhydride groups and epoxy groups can achieve chain extension, branching, and local network structure construction in the molten state, thereby improving the melt strength, interfacial adhesion, and thermal stability of the material. If epoxy resin can be further introduced into the EVA-g-MAH base for melt reaction, it is expected to construct a novel functionalized polymer system with high polarity, controllable branching structure, and excellent processing performance.
[0006] However, current research on the continuous reactive extrusion preparation of functionalized polymer systems from EVA-g-MAH and epoxy resin is still limited, especially lacking a process system that balances grafting stability, reaction efficiency, structural controllability, and industrial applicability. Therefore, developing a stable, structurally controllable, high-performance EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer system suitable for continuous industrial production and its preparation method is of significant theoretical and practical value. Summary of the Invention
[0007] In view of this, the present invention provides a functionalized polymer of EVA grafted with maleic anhydride and its preparation method. The present invention uses a composite free initiation system to melt graft and modify EVA, so that maleic anhydride is stably grafted onto the EVA molecular chain. Furthermore, through reactive extrusion process, the ring-opening reaction between the anhydride group and the epoxy group is realized, thereby constructing a functionalized polymer system with chain extension, branching and local network structure.
[0008] To achieve the above effects, the present invention adopts the following technical solution: In a first aspect, the present invention provides an EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer, comprising the following components in parts by weight: 80-120 parts EVA, 1-5 parts maleic anhydride, 0.1-3 parts composite initiator, 0.1-3 parts antioxidant, 0.5-10 parts epoxy resin, 0.1-5 parts auxiliary stabilizer, 0.1-5 parts lubricant, and 0.1-5 parts processing aid.
[0009] Furthermore, the vinyl acetate content of the EVA is 15-35 wt%, and the melt index is 2-10 g / 10 min; the EVA is selected from any one or more ethylene-vinyl acetate copolymers with a VA content of 18%, 20%, 24%, 28%, or 33%.
[0010] Furthermore, the composite initiator is composed of diisopropylbenzene peroxide (DCP) and 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane. Preferably, the mass ratio of DCP to 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane is 1:5 to 5:1.
[0011] Furthermore, the antioxidant includes any one or more of hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants. The hindered phenolic antioxidant is Irganox 1010. The phosphite antioxidant is Irgafos 168. The thioester antioxidant is DLTDP.
[0012] Furthermore, the epoxy resin is selected from any one or more of bisphenol A type epoxy resin, alicyclic epoxy resin, and multifunctional epoxy resin. The epoxy value of the epoxy resin is 0.35 to 0.60 eq / 100g.
[0013] Furthermore, the lubricant is selected from one or more of polyethylene wax, liquid paraffin, and stearate; the processing aid is selected from one or more of phosphate ester processing aids, flow modifiers, and dispersants.
[0014] Secondly, the present invention also provides a method for preparing the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer, comprising the following steps: (1) Preparation of EVA-g-MAH EVA, maleic anhydride, and composite initiator were mixed evenly in a certain proportion, and then a melt grafting reaction was carried out to obtain EVA-g-MAH. (2) EVA-g-MAH reacts with epoxy resin and is extruded The EVA-g-MAH, epoxy resin, antioxidant, lubricant and processing aid are mixed and subjected to melt reaction extrusion to obtain a functionalized polymer system.
[0015] Further, the mixing time in step (1) is 3 to 10 minutes; the melt grafting reaction in step (1) is carried out by a twin-screw extruder; the length-to-diameter ratio of the twin-screw extruder is 32 to 48; the melt grafting reaction temperature is 160 to 200°C; the screw speed of the twin-screw extruder is 100 to 400 rpm; and the vacuum devouring pressure in step (1) is -0.08 to -0.095 MPa.
[0016] Furthermore, the reaction temperature in step (2) is 130-180℃; the reaction time is 30-180s; the screw speed in step (2) is 120-300rpm; and the devolatilization temperature in step (2) is 130-150℃.
[0017] Furthermore, the product obtained in step (2) is granulated into final granular material after being pulled into strips.
[0018] Thirdly, the present invention also provides the application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer in the fields of polymer material modification and cement-based building materials.
[0019] Due to the synergistic effect of grafted maleic anhydride and epoxy functional groups, this functionalized polymer can form a good interfacial bond with cement hydration products and aggregate surfaces, improving the compatibility and adhesion between the polymer and the inorganic matrix. Simultaneously, it forms a continuous or semi-continuous polymer network structure during cement hardening, effectively improving the material's flexibility, crack resistance, impact resistance, and interfacial bond strength, while reducing the risk of drying shrinkage cracking. Furthermore, this material can optimize the pore structure of cement-based materials, improving their impermeability, freeze-thaw resistance, and durability, making it particularly suitable for concrete repair mortars, structural reinforcement materials, rapid repair materials, and high-performance sulfoaluminate cement-based composite materials.
[0020] In this invention, when the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer is applied to sulfoaluminate cement repair materials, the functionalized polymer prepared by this invention can form a composite interface structure at the interface between new and old concrete, which combines chemical bonding, mechanical interlocking, and polymer bridging effects. This significantly improves the interfacial bonding strength and durability between the repair layer and the substrate, inhibits the generation and propagation of interfacial microcracks, and thus enhances the overall service performance and service life of the repair structure. Simultaneously, the active functional groups introduced by grafting maleic anhydride and epoxy resin can enhance the interfacial interaction between the polymer and cement hydration products, optimize the microstructure of the interfacial transition zone, and improve the impermeability, crack resistance, and long-term service stability of the repair material. Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a melt free radical grafting process to stably graft maleic anhydride onto the EVA molecular chain, which significantly improves the polarity and surface activity of the material and enhances the interfacial compatibility and interfacial bonding ability between EVA and polar polymers, inorganic fillers and cement-based materials.
[0021] (2) This invention further utilizes the anhydride groups in the grafted segments to undergo a ring-opening reaction with the epoxy groups in the epoxy resin, constructing chain extension and branching structures between polymer molecular chains, thereby forming a functionalized system with certain three-dimensional network characteristics. This structure not only improves the melt strength and thermal stability of the material, but also enhances its mechanical properties, dimensional stability, and resistance to melt fracture during processing, providing a good structural basis for applications in highly filled systems and complex working conditions.
[0022] (3) This invention employs twin-screw reactive extrusion technology to achieve integrated continuous preparation of EVA grafted with maleic anhydride and epoxy resin chain extension and branching. It has advantages such as short process flow, high reaction efficiency, stable production process, good product quality consistency, and strong controllability. This process does not require complex post-processing steps, has strong equipment versatility, and is easy to realize large-scale industrial production, with high economic benefits and industrialization promotion value. At the same time, the raw materials used are all general-purpose industrial polymers and additives, with stable sources and controllable costs. There is no need to use organic solvents and complex post-processing. The entire preparation process is green and environmentally friendly, easy to operate, and can effectively reduce production costs and energy consumption, meeting the requirements of green manufacturing and clean production.
[0023] (4) The functionalized polymer prepared by this invention possesses excellent interfacial adhesion, mechanical properties, heat resistance, and processing stability. It can be widely used in low-smoke halogen-free cable materials, polyamide toughening modification systems, polyester blends, highly filled polymer composites, hot melt adhesives, and interfacial bonding materials. In particular, it shows good application prospects in improving the interfacial bonding strength between polymers and inorganic materials and improving the comprehensive performance of composite materials. At the same time, this material can also be used as a high-performance polymer modifier in cement-based and concrete materials. By improving the interfacial bonding between cement hydration products and aggregates, improving the toughness and crack resistance of materials, reducing porosity, and enhancing durability, it can improve the mechanical properties and service life of concrete. It has good application prospects in building repair materials, waterproof mortar, self-leveling materials, and high-performance concrete.
[0024] (5) The functionalized polymer prepared by this invention can significantly improve the early and long-term mechanical properties, interfacial bonding properties, flexural strength, and impact resistance of sulfoaluminate cement rapid repair mortar, and effectively reduce shrinkage cracking sensitivity and permeability, thereby improving material durability. Especially in engineering applications such as road pothole repair, highway emergency repair, and rapid repair of airport runways and bridge structures, it can achieve rapid strength development and meet the demand for rapid traffic reopening, demonstrating excellent engineering applicability and service reliability. Furthermore, this material can also be widely used as a compatibilizer or toughening modifier in the fields of low-smoke halogen-free cable materials, polyamide toughening systems, polyester blends, and hot melt adhesives, demonstrating good multi-system compatibility and application expansion. In summary, this invention has significant advantages in structural design, preparation process, and application performance. It not only achieves functionalized control of polymer structure but also expands its application scope in cement-based rapid repair materials and polymer composite materials, possessing important theoretical significance and broad industrial application value. Detailed Implementation
[0025] This invention provides an EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer system and its preparation method. By combining melt free radical grafting with epoxy chain extension reaction, maleic anhydride polar groups are introduced onto the EVA molecular chain, and further branched and local network structures are constructed, thereby obtaining a functionalized polymer material with high polarity, excellent interfacial compatibility, and good processability. This method employs a twin-screw reactive extrusion process to achieve continuous preparation, which is stable, efficient, and easily scaled up industrially, possessing a good foundation for industrial application.
[0026] In a first aspect, the present invention provides an EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer, comprising the following components in parts by weight: 80-120 parts EVA, 1-5 parts maleic anhydride, 0.1-3 parts composite initiator, 0.1-3 parts antioxidant, 0.5-10 parts epoxy resin, 0.1-5 parts lubricant, and 0.1-5 parts processing aid.
[0027] In some embodiments of the present invention, the vinyl acetate content of the EVA is 15-35 wt%, and the melt index is 2-10 g / 10 min.
[0028] In some embodiments of the present invention, the EVA is selected from any one or more of ethylene-vinyl acetate copolymers with a VA content of 18%, 20%, 24%, 28%, or 33%.
[0029] In some embodiments of the present invention, the maleic anhydride is industrial-grade maleic anhydride with a purity of not less than 98%.
[0030] In some embodiments of the present invention, the composite initiator is composed of diisopropylbenzene peroxide (DCP) and 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane. Preferably, the mass ratio of DCP to 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane is 1:5 to 5:1.
[0031] This invention employs a composite initiator synergistic initiation system. Through the phased action of initiators at different decomposition temperatures, it achieves continuous and uniform release of free radicals, effectively reducing the degradation of EVA molecular chains and cross-linking side reactions caused by excessively high local free radical concentrations, and improving the efficiency and uniformity of maleic anhydride grafting reaction.
[0032] In some embodiments of the present invention, the antioxidant includes any one or more of hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants. Preferably, the hindered phenolic antioxidant is Irganox 1010. The phosphite antioxidant is Irgafos 168. The thioester antioxidant is DLTDP.
[0033] In some embodiments of the present invention, the epoxy resin is selected from any one or more of bisphenol A type epoxy resin, alicyclic epoxy resin, and multifunctional epoxy resin. Preferably, the multifunctional epoxy resin is selected from any one or a combination of at least two of phenolic epoxy resin, biphenyl epoxy resin, bisphenol A type phenolic epoxy resin, o-cresol type phenolic epoxy resin, and dicyclopentadiene phenolic epoxy resin. Preferably, the epoxy value of the epoxy resin is 0.35 to 0.60 eq / 100g.
[0034] In some embodiments of the present invention, the lubricant is selected from one or more of polyethylene wax, liquid paraffin, and stearate.
[0035] In some embodiments of the present invention, the phosphate ester processing aid is selected from any one or more of resorcinol tetraphenyl diphosphate, triphenyl phosphite, and trinonylphenyl phosphite.
[0036] Secondly, the present invention also provides a method for preparing the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer, comprising the following steps: (1) Preparation of EVA-g-MAH EVA, maleic anhydride, and composite initiator were mixed evenly in a certain proportion, and then a melt grafting reaction was carried out to obtain EVA-g-MAH. (2) EVA-g-MAH reacts with epoxy resin and is extruded The EVA-g-MAH, epoxy resin, antioxidant, lubricant and processing aid are mixed and subjected to melt reaction extrusion. Functionalized branched structures are constructed through the ring-opening reaction between acid anhydride groups and epoxy groups to obtain a functionalized polymer system.
[0037] I. EVA-g-MAH grafting mechanism This invention employs a peroxide-initiated molten free radical grafting method to perform polar functionalization modification on EVA. Under high-temperature conditions, the initiator decomposes to form free radicals, which further abstract hydrogen from the EVA backbone to generate EVA macromolecular free radicals, which then undergo an addition reaction with MAH to form an EVA-g-MAH structure.
[0038] Its reaction mechanism includes the following processes: (1) The initiator undergoes thermal decomposition to form free radicals; (2) Free radicals abstract hydrogen from the EVA backbone to form macromolecular free radicals; (3) MAH undergoes addition with EVA free radicals to form a graft structure; (4) Some free radicals may couple to form a slightly branched structure; (5) Side reactions include MAH homopolymerization, EVA chain scission and excessive crosslinking.
[0039] This invention effectively reduces the probability of side reactions through the design of a composite initiator. Since DCP and 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane have different decomposition temperatures, the staged release of free radicals can be achieved, making the reaction process more stable.
[0040] Furthermore, this invention employs a synergistic system of primary and secondary antioxidants, wherein hindered phenolic antioxidants can capture high molecular free radicals, while phosphite-based secondary antioxidants can decompose hydrogen peroxides, thereby improving the thermal stability of the system.
[0041] II. Twin-screw reactive extrusion process This invention uses a co-rotating parallel twin-screw extruder to realize the grafting and reactive extrusion process.
[0042] In this invention, the twin-screw extruder not only serves as a conveying device, but also functions as a mixer, reactor, and mass transfer unit.
[0043] The twin-screw structure and its function mainly include: (1) Feeding and conveying area; EVA is first preheated at 80-100℃; (2) Melting and plasticizing zone; plasticization is completed at 140-160℃ to form a homogeneous melt; (3) Reaction mixing zone; MAH and initiator are added by liquid injection or side feeding, and uniform dispersion is achieved under the action of kneading block and shear element; the temperature of the reaction zone is controlled at 160~200℃ to ensure that MAH has sufficient reactivity and to avoid significant deacetic acid degradation of EVA. (4) Vacuum devolatilization zone; After the reaction is completed, the system enters the vacuum devolatilization zone, where unreacted MAH and volatile byproducts are removed by a negative pressure environment of -0.08 to -0.095 MPa; (5) Metering extrusion zone: The final melt is extruded through the die head and then granulated by air cooling or water cooling to obtain the final product.
[0044] III. Reaction Mechanism between EVA-g-MAH and Epoxy Resin After preparing EVA-g-MAH, this invention further utilizes the anhydride groups on its molecular chain to undergo a ring-opening grafting reaction with the epoxy groups in the epoxy resin. During the reaction, the anhydride groups and epoxy groups form chemical bonds, stably introducing epoxy resin structural units into the EVA molecular chain, forming an EVA-g-EP functionalized polymer system.
[0045] Through this reaction, EVA-g-MAH not only retains the high polarity and reactivity of maleic anhydride grafting, but also further acquires the excellent performance characteristics of epoxy resin. Because epoxy resin molecules contain highly reactive epoxy functional groups and rigid aromatic structures, their introduction significantly improves the material's interfacial adhesion, mechanical strength, heat resistance, and dimensional stability. Simultaneously, the residual epoxy functional groups can further react with active groups such as hydroxyl, amino, and carboxyl groups, giving the material even stronger interfacial reactivity and chemical bonding capabilities.
[0046] For cement-based material systems, the introduced epoxy functional groups can generate stronger interfacial interactions with the active groups on the surface of cement hydration products, promoting the formation of a stable bonding interface between the polymer and the inorganic matrix. For polyamide, polyester, and inorganic filler systems, it can improve interfacial compatibility and interfacial transfer efficiency, thereby improving the overall performance of the composite material.
[0047] Therefore, this invention achieves multifunctional synergistic reinforcement by grafting anhydride groups with epoxy groups through reaction of anhydride groups and epoxy groups, so that the resulting EVA-g-EP functionalized polymer simultaneously possesses the flexibility of EVA, the high polarity imparted by MAH, and the excellent adhesion, reactivity and structural stability of epoxy resin.
[0048] In some embodiments of the present invention, step (1) is carried out in a high-speed mixer for a mixing time of 3 to 10 minutes.
[0049] In some embodiments of the present invention, step (1) involves a melt grafting reaction performed using a twin-screw extruder with an aspect ratio of 32 to 48.
[0050] In some embodiments of the present invention, the melt grafting reaction temperature in step (1) is 160 to 200°C.
[0051] In some embodiments of the present invention, the screw speed of the twin-screw extruder in step (1) is 100 to 400 rpm.
[0052] In some embodiments of the present invention, the vacuum devouring pressure in step (1) is -0.08 to -0.095 MPa.
[0053] In some embodiments of the present invention, the epoxy resin in step (2) is added by side feeding or liquid injection.
[0054] In some embodiments of the present invention, the reaction temperature in step (2) is 130-180°C; the reaction time is 30-180s; and the screw speed in step (2) is 120-300rpm.
[0055] In some embodiments of the present invention, the devolatilization temperature in step (2) is 130 to 150°C.
[0056] In some embodiments of the present invention, the product obtained in step (2) is granulated into final granular material after being pulled into strips.
[0057] This invention further achieves a synergistic balance between material grafting efficiency, reaction stability, and processing performance by optimizing the structure of the twin-screw extruder, temperature distribution, vacuum devolatilization process, and additive system.
[0058] Thirdly, the present invention also provides the application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer in the fields of polymer material modification and cement-based building materials. Preferably, the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer is used in low-smoke halogen-free cable materials, polyolefin toughening systems, polyamide compatible modification systems, polyester blend systems, hot melt adhesive materials, interfacial bonding materials, polymer composite materials, and sulfoaluminate cement-based materials.
[0059] In some embodiments of the present invention, the application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer provided by the present invention in the sulfoaluminate cement repair mortar system, wherein the dosage of the functionalized polymer is 0-9 wt% (not 0) of the mass of the cementitious material; preferably, the dosage of the functionalized polymer is 3-9 wt% of the mass of the cementitious material; more preferably, the dosage of the functionalized polymer is 6 wt% of the mass of the cementitious material.
[0060] In some embodiments of the present invention, the application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer provided by the present invention in a low-smoke halogen-free flame-retardant cable material system, wherein the amount of the functionalized polymer is 0-9 wt% (not 0) of the mass of the cementitious material; preferably, the amount of the functionalized polymer is 3-9 wt% of the mass of the cementitious material; more preferably, the amount of the functionalized polymer is 6 wt% of the mass of the cementitious material.
[0061] In some embodiments of the present invention, the application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer provided by the present invention in the PA6 / PA66 engineering plastic system, wherein the amount of the functionalized polymer is 0-9 wt% (not 0) of the mass of the cementitious material; preferably, the amount of the functionalized polymer is 3-9 wt% of the mass of the cementitious material; more preferably, the amount of the functionalized polymer is 6 wt% of the mass of the cementitious material.
[0062] In some embodiments of the present invention, the application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer provided by the present invention in PET / EVA and PBT / EVA blend systems, wherein the amount of the functionalized polymer is 0-9 wt% (not 0) of the mass of the cementitious material; preferably, the amount of the functionalized polymer is 3-9 wt% of the mass of the cementitious material; more preferably, the amount of the functionalized polymer is 6 wt% of the mass of the cementitious material.
[0063] In some embodiments of the present invention, the application of the EVA-grafted maleic anhydride modified epoxy resin functionalized polymer provided by the present invention in packaging hot melt adhesives, wood adhesives and building sealant systems, wherein the amount of the functionalized polymer is 0-9 wt% (not 0) of the mass of the cementitious material; preferably, the amount of the functionalized polymer is 3-9 wt% of the mass of the cementitious material; more preferably, the amount of the functionalized polymer is 6 wt% of the mass of the cementitious material.
[0064] In engineering applications, the EVA-g-EP functionalized polymer obtained in this invention can be directly used as a functional modification component in sulfoaluminate cement rapid repair mortar systems. Relying on its highly polar functional group structure and controllable branched network structure, this material can significantly improve the interfacial bonding performance between the polymer and cement hydration products, constructing a continuous or semi-continuous toughening network structure during cement hardening, thereby effectively enhancing the early strength development capacity, flexural strength, and impact resistance of the repair mortar.
[0065] Combining the rapid setting and hardening characteristics of sulfoaluminate cement, the material of this invention enables rapid strength formation in the repair system, allowing the repair mortar to meet the mechanical requirements for reopening to traffic in a short time. This satisfies the engineering needs of highway pothole repair, urban road emergency repair, and rapid bridge deck maintenance. Simultaneously, this material exhibits excellent fatigue and impact resistance in airport runway and apron repair applications, effectively resisting the high-frequency cyclic loads caused by aircraft takeoffs and landings, significantly improving the service safety and durability of the repaired area.
[0066] Furthermore, the functionalized polymers of this invention can improve the internal pore structure of cement-based materials, reduce permeability and shrinkage cracking sensitivity, and enhance the freeze-thaw resistance and long-term durability of the repair layer, thereby extending the service life of engineering projects. Under different admixture conditions (0%–9%), the material properties exhibit good controllability, with optimal overall performance achieved around 6 wt%, facilitating engineering formulation design and standardized promotion.
[0067] In summary, this invention is not only applicable to the fields of low-smoke halogen-free cable materials, polyamide toughening, polyester blends and hot melt adhesives, but can also serve as a key functional component of sulfoaluminate cement-based rapid repair mortar, enabling rapid repair and efficient maintenance of infrastructure such as roads, bridges, airport runways and industrial floors. It has significant industrial application value and engineering promotion prospects.
[0068] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0069] Unless otherwise specified, the test methods or experimental methods described in the following examples are all conventional methods; unless otherwise specified, the raw materials and additives are obtained from conventional commercial sources or prepared by conventional methods.
[0070] The properties of the material obtained in this invention were characterized using the following methods: (1) FTIR infrared analysis: by detecting 1780~1850cm -1 The characteristic absorption peaks of acid anhydrides and the changes in ester bond absorption peaks after epoxide reaction were analyzed qualitatively to assess the grafting and reaction conditions.
[0071] (2) Acid-base titration method: The grafting rate was calculated by titration using the KOH-ethanol system and the HCl-isopropanol system.
[0072] (3) DSC analysis: Differential scanning calorimetry is used to analyze the changes in the material’s crystallization temperature, melting temperature and crystallization behavior.
[0073] (4) GPC analysis: The molecular weight and distribution changes of the material were determined by gel permeation chromatography.
[0074] (5) Rheological property analysis: The degree of branching and melt stability of the material are evaluated by melt rheological testing.
[0075] (6) Gel content test: used to evaluate the crosslinking level of materials.
[0076] (7) Mechanical property testing: including tensile strength (measured by universal testing machine), elongation at break, impact strength and peel strength test (180° peel method).
[0077] (8) Thermal stability analysis: Thermogravimetric analysis (TGA) was used to evaluate the thermal and oxygen stability of the material.
[0078] (9) Melt Flow Index (MFI) test: The MFI is measured using a melt flow rate meter.
[0079] 2,5-Dimethyl-2,5-bis(tert-butylperoxide)hexane, abbreviated as AD, is also known as bis(2,5)-pentane sulfide, CAS number 78-63-7.
[0080] Example 1 A method for preparing EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer, the specific steps of which are as follows: (1) Preparation of EVA-g-MAH 45g of maleic anhydride, 2g of DCP, and 2g of 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane were mixed and then added to 2942g of EVA resin. The mixture was stirred in a high-speed mixer for 5 minutes, followed by melt grafting reaction extrusion using a twin-screw extruder with an L / D ratio of 40. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1: 90℃; Zone 2: 140℃; Zone 3: 165℃; Zone 4: 175℃; Zone 5: 180℃; Zone 6: 185℃; Die head temperature: 180℃; Screw speed: 220 rpm; Vacuum devolatilization pressure was controlled at -0.09 MPa to obtain EVA-g-MAH. (2) EVA-g-MAH reacts with epoxy resin and is extruded The EVA-g-MAH was mixed with 58.2g of epoxy resin, 7.5g of Irganox 1010, 4.5g of Irgafos 168, 12g of polyethylene wax, 8g of liquid paraffin, and 6g of resorcinol tetraphenyl diphosphate. The mixture was then subjected to melt reaction extrusion at 150℃ for 90s, with a screw speed of 160rpm and a devolatilization temperature of 140℃ to obtain a functionalized polymer system.
[0081] The EVA has a vinyl acetate content of 28% and a melt index of 10 g / 10 min.
[0082] The epoxy resin is bisphenol A type liquid epoxy resin E42. The epoxy value of the epoxy resin is 0.42 eq / 100g.
[0083] The results show that the obtained material has good melt stability and interfacial adhesion properties.
[0084] Example 2 The difference from Example 1 is that maleic anhydride is 60g; epoxy resin is 80g; and the screw speed is adjusted to 180rpm.
[0085] The results showed that the grafting rate of the material was further improved, but the melt viscosity of the system increased significantly.
[0086] Example 3 The difference from Example 1 is that 6g of 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane was used.
[0087] The results showed that the grafting uniformity of the material was further improved and the gel content was reduced.
[0088] Example 4 The difference from Example 1 is that the VA content of the EVA resin is 33%.
[0089] The results show that a higher VA content is beneficial to improving MAH grafting efficiency and interfacial compatibility.
[0090] Example 5 The difference from Example 1 is that the epoxy resin used is bisphenol A type high epoxy value epoxy resin E51, with an epoxy value of 0.51 eq / 100g. The results show that increasing the epoxy value is beneficial to improving the grafting efficiency of MAH.
[0091] Example 6 The difference from Example 1 is that the epoxy resin used is an alicyclic epoxy resin with an epoxy value of 0.73 eq / 100g. The results show that the grafting rate is further improved.
[0092] Example 7 The difference from Example 1 is that the VA content of the EVA resin is 24%.
[0093] The results show that a lower VA content is not conducive to improving MAH grafting efficiency and interfacial compatibility.
[0094] Comparative Example 1 The difference from Example 1 is that 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane was not added.
[0095] The results showed that obvious gel particles appeared in the system, and the material processing stability decreased.
[0096] Comparative Example 2 The difference from Example 1 is that there is no EP, that is, only EVA-g-MAH is prepared.
[0097] The results show that the material has low melt strength and insufficient interfacial adhesion.
[0098] Comparative Example 3 The difference from Example 1 is that the reaction temperature is increased to 210°C.
[0099] The results showed that EVA exhibited significant thermal degradation, turning the material yellow and reducing its mechanical properties.
[0100] Comparative Example 4 Unmodified EVA resin.
[0101] Comparative Example 5 The difference from Example 1 is that diisopropylbenzene peroxide (DCP) was not added.
[0102] Comparative Example 6 The difference from Example 1 is that the reaction extrusion temperature in step (2) is 120°C.
[0103] Comparative Example 7 The difference from Example 1 is that the reaction extrusion temperature in step (2) is 190°C.
[0104] Performance testing (i) Performance tests were conducted on Examples 1-7 and Comparative Examples 1-7. The tests included: grafting rate, density, melt flow index (MFI), thermal properties (melting point, glass transition temperature, Vicat softening point), mechanical properties (tensile strength, elongation at break, Young's modulus, and impact strength), water absorption, volume resistivity, dielectric constant, thermal decomposition temperature, and crystallinity. The specific test results are shown in Tables 1 and 2.
[0105] Table 1
[0106] Table 2
[0107] As shown in Tables 1 and 2, the grafting rates of Examples 1-7 of the present invention were stably controlled within the range of 1.71–1.86 wt%, the grafting rate of Comparative Example 1 was 1.61 wt%, the grafting rate of Comparative Example 5 was 1.54 wt%, the grafting rate of Comparative Example 6 was 1.17 wt%, and the grafting rate of Comparative Example 7 was 1.69 wt%. This indicates that the present invention, using a composite initiator and a specific reactive extrusion process, can significantly improve the grafting efficiency of maleic anhydride onto EVA molecular chains and ensure the stability and repeatability of the grafting reaction.
[0108] As shown in Tables 1 and 2, although the melt flow index of Examples 1-7 of the present invention is reduced, good processing flow properties are still maintained. Meanwhile, due to the chain extension and branching reactions between the anhydride groups and epoxy groups, the molecular weight of the material increases, and the melt strength is significantly improved, which is beneficial for subsequent extrusion molding and processing of high-filler systems.
[0109] As shown in Tables 1 and 2, the tensile strength of unmodified EVA in Comparative Example 4 was 14 MPa, and the peel strength was 1.8 N / mm; in Comparative Example 2, EVA-g-MAH, these values were increased to 14.9 MPa and 2.8 N / mm, respectively. In Examples 1-7 of this invention, the tensile strength reached 16.5–21 MPa, an increase of 20%–45% compared to unmodified EVA in Comparative Example 4; the peel strength reached 4.2–5.8 N / mm, an increase of 133%–222% compared to unmodified EVA. The results indicate that the introduction of epoxy resin chain extension and branching structures effectively enhanced the internal bonding strength and interfacial adhesion of the material.
[0110] As shown in Tables 1 and 2, the thermal decomposition initiation temperature of unmodified EVA in Comparative Example 4 was 300℃, while that of EVA-g-MAH was increased to 302℃. The thermal decomposition initiation temperatures of Examples 1-7 of this invention were further increased to 308-325℃, with Example 5 reaching 320℃, an increase of 20℃ compared to unmodified EVA. These results indicate that the branched structure formed by anhydride grafting and epoxy chain extension reactions can effectively improve the thermal stability and high-temperature performance of the material.
[0111] (ii) Interface compatibility test Using the PA / EVA blend system as a model system, the interfacial compatibility of the materials was evaluated, and the results are shown in Table 3.
[0112] Table 3
[0113] Table 3 shows that Comparative Example 4, the unmodified EVA and PA system exhibits significant phase separation; Comparative Example 2, EVA-g-MAH, shows only slight phase separation; all examples of this invention show uniformly dispersed microstructures, tight interfacial bonding, and stable phase structures. In contrast, Comparative Example 1 shows only localized aggregation of the single initiator, while Comparative Example 3 shows significant phase separation. This indicates that the EVA-g-EP functionalized polymer prepared in this invention can significantly improve the interfacial compatibility between PA and EVA, and enhance the structural uniformity and overall performance of the blend system.
[0114] Application examples Application Example 1 The functionalized polymer prepared in Example 1 of this invention is incorporated as a modifying component into a sulfoaluminate cement repair mortar system. The modified component, sulfoaluminate cement, graded sand, water, and water-reducing agent are combined to form a polymer-modified rapid repair mortar. The polymer-modified rapid repair mortar is composed of sulfoaluminate cement, graded sand, water, and a polycarboxylate-based water-reducing agent mixed in a mass ratio of 100:200:28:0.6.
[0115] (1) The amount of the modified component is 0 wt% of the mass of the cementitious material.
[0116] (2) The amount of the modified component is 3 wt% of the mass of the cementitious material.
[0117] (3) The amount of the modified component is 6 wt% of the mass of the cementitious material.
[0118] (4) The amount of the modified component is 9 wt% of the mass of the cementitious material.
[0119] Among them, (1)-(4) samples were prepared according to the same mix ratio and were molded and cured under the same curing conditions.
[0120] The early mechanical properties (1 h, 4 h and 1 d compressive strength), long-term mechanical properties (28 d compressive and flexural strength), interfacial bonding properties, impact resistance and durability properties (water absorption, drying shrinkage and freeze-thaw properties, etc.) of the repair mortar under different admixture conditions (1)-(4) of Application Example 1 were tested and compared. The test results are shown in Table 4 and Table 5.
[0121] Table 4
[0122] Table 5
[0123] As shown in Tables 4 and 5, with the increase of EVA-g-EP content, the compressive strength, flexural strength, interfacial bond strength, and impact resistance of the repair mortar are all significantly improved. The optimal values for all properties are achieved when the content is 6 wt%. Further increasing to 9 wt% results in a slight decrease in some mechanical properties due to the influence of excessive polymer on the continuity of cement hydration products, but these properties are still significantly better than those of the unmodified sample. Therefore, the preferred EVA-g-EP functionalized polymer content in this invention is 3–9 wt% of the cement mass, more preferably 6 wt%.
[0124] The working principle of Application Example 1 is as follows: The maleic anhydride grafting structure and epoxy chain-extended branching structure in the functionalized polymer of this invention can significantly enhance the interfacial interaction between the polymer and the hydration products of sulfoaluminate cement. During the material hardening process, the polymer gradually forms a continuous or semi-continuous network structure within the cement matrix, and interweaves with hydration products such as ettringite (AFt) and hydrated calcium aluminate gel to form a dense composite system, thereby improving the overall mechanical properties and interfacial bonding performance of the repair mortar.
[0125] Compared to unpolymer-modified sulfoaluminate cement repair materials, the modified repair mortar of this invention exhibits a higher early strength development rate. Leveraging the rapid setting and hardening characteristics of sulfoaluminate cement itself, along with the toughening and reinforcing effects of the polymer, the repair material can quickly achieve high load-bearing capacity, meeting the requirements for rapid traffic reopening and emergency repair construction. Simultaneously, the flexible polymer segments effectively alleviate shrinkage stress during cement hardening, improve the material's deformation coordination, and significantly reduce the risk of cracking in the repair layer.
[0126] Furthermore, the numerous polar functional groups introduced by grafting maleic anhydride and epoxy resin enhance the interfacial adhesion between the polymer and the old concrete matrix, thus forming a strong bond between the repair layer and the original concrete. This interface simultaneously possesses mechanical interlocking, polymer bridging, and chemical bonding effects, effectively inhibiting interfacial debonding and crack propagation, and improving the synergistic stress-bearing capacity and long-term service stability between the new and old concrete.
[0127] The modified repair mortar of this invention exhibits excellent flexural and impact resistance. The flexible network structure formed by the polymer can absorb and disperse stress concentration caused by external loads, improving the material's toughness and overcoming the brittleness of traditional sulfoaluminate cement repair materials. Under vehicle loads, aircraft take-off and landing impact loads, and cyclic fatigue loads, the repaired area can still maintain good structural integrity and durability.
[0128] Meanwhile, the polymer of this invention can improve the pore structure of cement-based materials, reduce capillary connectivity, and increase material density, thereby enhancing the impermeability, freeze-thaw resistance, chloride ion corrosion resistance, and wear resistance of the repair material, and extending the service life of the repair structure.
[0129] Therefore, the functionalized polymers of this invention are particularly suitable for highway pothole repair, rapid urban road repair, bridge deck pavement repair, rapid airport runway and apron maintenance, port and dock concrete structure maintenance, industrial floor repair, and various high-performance sulfoaluminate cement-based rapid repair materials. They can achieve the comprehensive goals of rapid construction, rapid recovery of use, high early strength, high flexural strength, and excellent durability.
[0130] Application Example 2 The functionalized polymer prepared in Example 1 of this invention was used as a compatibilizer and interface reinforcing agent in a low-smoke halogen-free flame-retardant cable material system. The low-smoke halogen-free flame-retardant cable material is composed of ethylene-vinyl acetate copolymer (EVA), linear low-density polyethylene (LLDPE), magnesium hydroxide flame retardant, antioxidant, lubricant, and the functionalized polymer prepared in Example 1 of this invention. The components, by mass parts, are: EVA 40 parts, LLDPE 20 parts, magnesium hydroxide 140 parts, antioxidant 1010 0.5 parts, and lubricant EBS (ethylene bis-stearamide) 1.0 part. The amount of the functionalized polymer added is 0 wt%, 3 wt%, 6 wt%, and 9 wt% of the total polymer matrix mass, respectively, while the proportions of the remaining components remain consistent. The low-smoke halogen-free flame-retardant cable material sample was prepared by high-speed mixing and twin-screw melt extrusion granulation.
[0131] (1) The amount of the functionalized polymer added is 0 wt%.
[0132] (2) The amount of the functionalized polymer added is 3 wt%.
[0133] (3) The amount of the functionalized polymer added is 6 wt%.
[0134] (4) The amount of the functionalized polymer added is 9 wt%.
[0135] Among them, (1)-(4) are prepared by keeping the proportions of flame-retardant filler and other components consistent.
[0136] The mechanical properties, processing properties, electrical insulation properties and filler dispersion effect of the samples under different doping conditions (1)-(4) of Application Example 2 were tested. The test results are shown in Table 6.
[0137] Table 6
[0138] Table 6 shows that with the increase of EVA-g-EP functionalized polymer addition, the tensile strength, elongation at break, and electrical insulation properties of the low-smoke halogen-free flame-retardant cable material are significantly improved, while maintaining excellent flame-retardant properties. When the addition amount is 6%, the overall performance reaches its optimal level, indicating that the functionalized polymer can significantly improve the interfacial bonding ability between the EVA matrix and the inorganic flame-retardant filler, improve the uniformity of filler dispersion, and thus enhance the overall performance of the material. When the addition amount is further increased to 9%, some properties decrease slightly, but overall it is still significantly better than the control group without polymer. Therefore, the preferred addition amount of EVA-g-EP functionalized polymer in the low-smoke halogen-free flame-retardant cable material is 3%–9%, more preferably 6%.
[0139] Application Example 3 The functionalized polymer prepared in Example 1 of this invention was used as a reactive toughening agent and compatibilizer in a PA6 / PA66 engineering plastic system. The PA6 / PA66 engineering plastic composite material is composed of PA6, PA66, antioxidant, lubricant, and the functionalized polymer of this invention. The components, by mass parts, are: PA6 60 parts, PA66 40 parts, antioxidant 1010 0.5 parts, and lubricant EBS (ethylene bis-stearamide) 0.3 parts. The amount of the functionalized polymer added is 0 wt%, 3 wt%, 6 wt%, and 9 wt% of the total mass of the polyamide resin, respectively, while the proportions of the remaining components remain consistent. After high-speed mixing, the components are melt-blended, extruded and granulated using a twin-screw extruder, and then injection-molded into standard samples for performance testing.
[0140] (1) The amount of the functionalized polymer added is 0 wt%.
[0141] (2) The amount of the functionalized polymer added is 3 wt%.
[0142] (3) The amount of the functionalized polymer added is 6 wt%.
[0143] (4) The amount of the functionalized polymer added is 9 wt%.
[0144] Among them, composite materials are prepared under the same processing conditions.
[0145] The mechanical properties, interfacial bonding properties and impact properties of the samples under different doping conditions (1)-(4) of Application Example 3 were tested, and the test results are shown in Table 7.
[0146] Table 7
[0147] Table 7 shows that with the increase of the added amount of EVA-g-EP functionalized polymer, the impact toughness, elongation at break, and interfacial bonding performance of the polyamide system are significantly improved. When the added amount is 6%, the overall performance of the material reaches its optimal level. The anhydride groups in the polymer can react with the terminal amino groups of the polyamide, improving the interfacial bonding between the two phases and gradually changing the fracture mode from brittle fracture to ductile fracture. When the added amount continues to increase to 9%, some properties decrease slightly due to the increased polymer phase content, but are still significantly better than the unmodified sample. Therefore, the preferred added amount of EVA-g-EP functionalized polymer in the polyamide toughening system is 3%–9%, more preferably 6%.
[0148] Application Example 4 The functionalized polymer prepared in Example 1 of this invention was used as a reactive compatibilizer in PET / EVA and PBT / EVA blend systems. The PET / EVA blend materials were composed of PET, EVA, antioxidant, lubricant, and the functionalized polymer of this invention. The components, by mass, were: 70 parts PET, 30 parts EVA, 0.5 parts antioxidant 1010, and 0.3 parts lubricant EBS (ethylene bis-stearamide). The amounts of the functionalized polymer added were 0 wt%, 3 wt%, 6 wt%, and 9 wt% of the total polymer mass, respectively, while the proportions of the remaining components remained consistent. After high-speed mixing, the components were melt-blended, extruded, granulated, and injection-molded into standard samples for performance testing using a twin-screw extruder.
[0149] (1) The amount of the functionalized polymer added is 0 wt%.
[0150] (2) The amount of the functionalized polymer added is 3 wt%.
[0151] (3) The amount of the functionalized polymer added is 6 wt%.
[0152] (4) The amount of the functionalized polymer added is 9 wt%.
[0153] Among them, blended materials are prepared under the same processing conditions.
[0154] The mechanical properties, interfacial bonding properties and impact properties of the samples under different doping conditions (1)-(4) of Application Example 4 were tested, and the test results are shown in Table 7.
[0155] Table 8
[0156] As shown in Table 8, the mechanical properties, heat resistance, and dimensional stability of the blend system are significantly improved with the increase of the added amount of EVA-g-EP functionalized polymer. The overall material performance is optimal when the added amount is 6%, as the functionalized polymer effectively reduces the interfacial tension between PET (or PBT) and EVA, improves the uniformity of dispersion between the two phases, and enhances the interfacial bonding strength. When the added amount is further increased to 9%, the material performance decreases slightly, but it is still significantly better than the unmodified sample. Therefore, the preferred addition amount of EVA-g-EP functionalized polymer in the polyester blend system is 3%–9%, more preferably 6%.
[0157] The functionalized polymer prepared in Example 1 of this invention was used as a reactive compatibilizer in a PBT / EVA blend system, i.e., PBT was used to replace PET in an equal amount, while other conditions remained unchanged. Testing showed that the experimental results were not significantly different from those obtained when applied to the PET / EVA system (p>0.05).
[0158] Application Example 5 The functionalized polymer prepared in Example 1 of this invention was applied to packaging hot melt adhesives, wood adhesives, and building sealant systems. The adhesive material consisted of EVA resin, tackifying resin, paraffin wax, antioxidant 1010, and the functionalized polymer of this invention. The components, by weight, were: 40 parts EVA resin, 45 parts tackifying resin, 14 parts paraffin wax, and 1 part antioxidant 1010. The amount of the functionalized polymer added was 0 wt%, 3 wt%, 6 wt%, and 9 wt% of the total mass of the adhesive material, while the remaining components maintained the same proportions. The adhesive material samples were prepared by melt mixing and uniform stirring of all components.
[0159] (1) The amount of the functionalized polymer added is 0 wt%.
[0160] (2) The amount of the functionalized polymer added is 3 wt%.
[0161] (3) The amount of the functionalized polymer added is 6 wt%.
[0162] (4) The amount of the functionalized polymer added is 9 wt%.
[0163] Among them, adhesive materials are prepared under the same preparation process conditions.
[0164] The bonding performance and heat resistance of the samples under different dosage conditions (1)-(4) of Application Example 5 were tested, and the test results are shown in Table 7.
[0165] Table 9
[0166] As shown in Table 9, with the increase of the added amount of EVA-g-EP functionalized polymer, the initial tack, holding power, peel strength, and heat resistance of the hot melt adhesive system are significantly improved. When the added amount is 6%, all properties reach their optimal levels, indicating that the anhydride groups and epoxy structure can significantly improve the material's adhesion to substrates such as metals, wood, plastics, and concrete, and enhance interfacial bonding stability. When the added amount is further increased to 9%, some properties decrease slightly, but are still significantly better than the sample without added polymer. Therefore, the preferred added amount of EVA-g-EP functionalized polymer in hot melt adhesives and interfacial bonding materials is 3%–9%, more preferably 6%.
[0167] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A functionalized polymer of EVA grafted with maleic anhydride and modified epoxy resin, characterized in that, By weight, it comprises the following components: 80-120 parts EVA, 1-5 parts maleic anhydride, 0.1-3 parts composite initiator, 0.1-3 parts antioxidant, 0.5-10 parts epoxy resin, 0.1-5 parts lubricant, and 0.1-5 parts processing aid.
2. The EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 1, characterized in that, The EVA has a vinyl acetate content of 15-35 wt% and a melt index of 2-10 g / 10 min; the EVA is selected from any one or more ethylene-vinyl acetate copolymers with a VA content of 18%, 20%, 24%, 28% or 33%.
3. The EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 1, characterized in that, The composite initiator is composed of diisopropylbenzene peroxide and 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane.
4. The EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 1, characterized in that, The antioxidants include any one or more of hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants.
5. The EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 1, characterized in that, The epoxy resin is selected from any one or more of bisphenol A type epoxy resin, alicyclic epoxy resin, and multifunctional epoxy resin.
6. The EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 1, characterized in that, The lubricant is selected from any one or more of polyethylene wax, liquid paraffin, and stearate; the processing aid is selected from any one or more of phosphate ester processing aids, flow modifiers, and dispersants.
7. The method for preparing the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Preparation of EVA-g-MAH EVA, maleic anhydride, and composite initiator were mixed evenly in a certain proportion, and then a melt grafting reaction was carried out to obtain EVA-g-MAH. (2) EVA-g-MAH reacts with epoxy resin and is extruded The EVA-g-MAH, epoxy resin, antioxidant, lubricant and processing aid are mixed and subjected to melt reaction extrusion to obtain a functionalized polymer system.
8. The method for preparing the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 7, characterized in that, The mixing time in step (1) is 3 to 10 minutes; the melt grafting reaction in step (1) is carried out by a twin-screw extruder; the length-to-diameter ratio of the twin-screw extruder is 32 to 48; the process temperature of the twin-screw extruder is 160 to 200°C; the screw speed of the twin-screw extruder is 100 to 400 rpm; the vacuum devouring pressure in step (1) is -0.08 to -0.095 MPa.
9. The method for preparing the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to claim 7, characterized in that, The reaction temperature in step (2) is 130-180℃; the reaction time is 30-180s; the screw speed in step (2) is 120-300rpm; and the devolatilization temperature in step (2) is 130-150℃.
10. The application of the EVA-grafted maleic anhydride-modified epoxy resin functionalized polymer according to any one of claims 1-6, or the functionalized polymer prepared by the method according to any one of claims 7-9, in the fields of polymer material modification and cement-based building materials.
